Tradisi Penulisan Hadith dalam Karya Ulama’ Melayu: Kajian Terhadap Kitab ‘Aqidah al-Najin - Abdul Latif, Faizuri; Abdul Hamid, Ahmad Faisal (Jurnal Usuluddin, 2009)
Malay Muslim scholars have built a writing tradition that forms the framework of Islamic thought which cover the whole field of knowledge. They are very active in the production of works in various Islamic disciplines such as `Aqidah, Fiqh, Tasawwuf, and so forth. In order to strengthen their reasoning against the contention raised, they have provided various arguments and evidence including the evidence of Hadith. Therefore, this study is performed to review the pattern and form of writing the Hadith in the works of Malay Muslim scholars, focusing on `Aqidah al-Najin. The main factor of this work’s selection as the case study is due to the fact that it is one of the best works ever produced by Malay Muslim scholars. Beside that, there are many Hadith presented in this work.